The self-evaluation of teaching practice as a tool for improving the teaching and learning process of students - Bolancé García, Juana; Cuadrado Muñoz, Francisco; Ruiz Suárez, José Ramón; Sánchez Velasco, Fernando (Avances en Supervisión Educativa, 2013)
After a brief historical review leading us to understand where the focus has been placed to improve education over the course of recent years, we reach the present, in which several reports and studies emphasize the influences on what happens in the classroom, ie in the interaction between teacher and students. The autonomy of schools should necessarily be linked to self-assessment to meet the objective of improving the students’ learning. In this sense, teacher self-evaluation has to be a strategy that allows for the improvement of the school in general, as well as a process of continuous and collective professional development. From this perspective a proposal is presented (modeled on Intervention in Key Factors by the Educational Inspection of Andalusia) aimed at generating reflection at various levels (coordinating bodies, teachers, ...) regarding key factors such as curricula and evaluation, to assess in this way if this happens daily in class and to assure that the planning and the actual teaching in the classroom is adapted to the true needs of the students.